KAJIAN PENGARUH MANAJEMEN PENGETAHUAN TERHADAP PERFORMA ORGANISASI - Richard Vinc (Institut Bisnis dan Informatika Kwik Kian Gie, 2018)
Organizational knowledge management has been proven to assist the organization in achieving its goals and also provides competitive advantage, since its organizational knowledge and experience can make the decision-making process easier, precise and decisive. It can be stated that as long as the organizational knowledge is in good quality, it can be concluded that the performance of management will also grow significantly. Reflecting on many previous studies, this study uses systematic literature review towards 15 journal article and aims to provide practical guidance and direction on how an organization can manage its knowledge and what aspects to consider in order to improve its overall performance.Â Keywords: knowledge, knowledge management, organization performance